Flood risk assessment for Davao Oriental in the Philippines using geographic information system‐based multi‐criteria analysis and the maximum entropy model. Issue 2 (18th March 2020) - Cabrera, Jonathan Salar; Lee, Han Soo
Abstract: The assessments of flood‐prone areas and flood risk due to pluvial flooding for Davao Oriental on Mindanao Island in the Philippines were carried out by the analytic hierarchy process (AHP) and maximum entropy (Maxent) models using multiple criteria such as slope, elevation, soil type, rainfall, drainage density, distance to the main channel, and population density. Flood records from 70 survey points were obtained and used to verify the model results. The criteria weights of the top three important factors in the AHP are rainfall (42%), slope (23%), and elevation (15%), whereas those in the Maxent model are elevation (36%), rainfall (23%), and soil (19%). The verification results show that the accuracies of the AHP and Maxent model are 81 and 95.6%, respectively, indicating that both approaches are reliable in flood hazard and risk assessments. Approximately 22% of the total area and approximately 30% of the total population of Davao Oriental are classified as high risk of pluvial flooding in the current situation by the AHP method. This study shows a broad‐scale high‐level data‐driven screening method that can be used to help identify potential hot spots for pluvial flooding for which more detailed numerical modelling studies should be undertaken.